Facilitators to cervical cancer screening in a minority, urban, underserved population - Noel Higgason; Linh Nguyen; Yen-Chi Le; Ogochukwu Juliet Ezeigwe; Tong Han Chung; Natalia Williams; Xochitl K. Olguin; Abigail S. Zamorano (Elsevier, 2024)
Objectives: Cervical cancer has markedly declined due to widespread use of screening, but Hispanic women continue to bear a disproportionate amount of the cervical cancer burden due to under-screening. Previous studies have explored barriers to screening but have failed to identify targetable facilitators in this group. We aimed to assess facilitators to cervical cancer screening among a predominantly urban, Hispanic population who presented to a no-cost, community-based clinic. Methods: Patients completed demographic and health information, a validated social determinants of health (SDOH) screen, and a self-reported facilitators survey on factors which enabled them to present to clinic. Descriptive statistics were conducted to assess patients' sociodemographic characteristics, SDOH, and perceived facilitators. Results: 124 patients were included. 98 % were Hispanic, 90 % identified Spanish as their preferred language, and 94 % had no insurance. Median age was 41. 31 % of patients reported a history of abnormal screening. On SDOH, over 80 % of patients screened positive in at least one domain, with the most common being food insecurity (53 %) and stress (46 %). The most frequently reported facilitator was encouragement from a family member/friend (30 %). 26 % of patients reported time off from work and 25 % reported availability of child/elder care as facilitators. Conclusions: Identifying facilitators among patients who present for cervical cancer screening is critical to designing care plans to reach all populations. Our survey showed that the single greatest facilitator to patients presenting for cervical cancer screening was encouragement from a family member/friend. These findings suggest that increasing community involvement and awareness may help to improve cervical cancer screening in a minority, urban, underserved population.